The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1194/jlr.d070433
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative profiling of endocannabinoids and related N-acylethanolamines in human CSF using nano LC-MS/MS

Abstract: The endocannabinoid system has emerged as a crucial regulator of synaptic communication in the CNS (1-3). Dysregulation of this system is implicated in various neurological and psychiatric disorders, such as neuroinflammation, stroke, brain trauma, anxiety, and depression (4-8). The endocannabinoid system consists of endogenous lipid messengers (endocannabinoids) that activate two distinct cannabinoid (CB) (CB 1 and CB 2 ) receptors and the en-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 40 publications
2
13
0
3
Order By: Relevance
“…However, the on-line purification process was preceded by LLE with toluene, which improved the analyte extraction, recovery, and selectivity and minimized the 2-AG isomerization with respect to the different extraction solvents. Besides AEA, 2-AG, and its isomerization product, 1-AG, Fanelli et al also monitored some of the bioactive lipids in human plasma, namely N-acylethanolamines (NAEs), such as N-palmitoylethanolamine (PEA) and N-oleoylethanolamine (OEA), which are produced through the same biosynthetic pathway as AEA and have negligible or only weak affinity for both the CB1 and the CB2 receptors, but can indirectly modulate CBR activity by interfering with endocannabinoid metabolism [45,46]. The analytical method, which was based on positive MRM and made use of the stable isotope-labelled internal standards of all analytes, provided very good lower limits of quantification (LLOQ) [41], i.e., 0.020, 0.078, 0.078, 0.195, and 0.049 pmol/mL for AEA, 2-AG, 1-AG, PEA, and OEA, respectively.…”
Section: Detection Of Ecs In Biological Fluids Hair and Tissuesmentioning
confidence: 99%
“…However, the on-line purification process was preceded by LLE with toluene, which improved the analyte extraction, recovery, and selectivity and minimized the 2-AG isomerization with respect to the different extraction solvents. Besides AEA, 2-AG, and its isomerization product, 1-AG, Fanelli et al also monitored some of the bioactive lipids in human plasma, namely N-acylethanolamines (NAEs), such as N-palmitoylethanolamine (PEA) and N-oleoylethanolamine (OEA), which are produced through the same biosynthetic pathway as AEA and have negligible or only weak affinity for both the CB1 and the CB2 receptors, but can indirectly modulate CBR activity by interfering with endocannabinoid metabolism [45,46]. The analytical method, which was based on positive MRM and made use of the stable isotope-labelled internal standards of all analytes, provided very good lower limits of quantification (LLOQ) [41], i.e., 0.020, 0.078, 0.078, 0.195, and 0.049 pmol/mL for AEA, 2-AG, 1-AG, PEA, and OEA, respectively.…”
Section: Detection Of Ecs In Biological Fluids Hair and Tissuesmentioning
confidence: 99%
“…Kantae et al have shown that the use of nano-LC can extend the range of endocannabinoids and related molecules (e.g., N-acylethanolamines) to be detected simultaneously in cerebrospinal fluids . In this case, a chip-based nano-LC–MS/MS analysis was carried out.…”
Section: Lipidomicsmentioning
confidence: 99%
“…O processo de isomerização tem sido amplamente discutido na literatura e resultados demonstram que solventes polares próticos favorecem a conversão de 2-AG para 1-AG (Rouzer et al, 2002;Zoerner et al, 2012;Balvers et al, 2013;Docs et al, 2017). Em nosso estudo foi observado a conversão de 2-AG para 1-AG em amostras de plasma, o que pode ser explicado devido à grande quantidade de água presente em plasma (≅ 90%) (Krebs, 1950;Adkins et al, 2002) bem como a presença de albumina sérica (Zoerner et al, 2011;Garst et al, 2015;Kantae et al, 2017).…”
Section: Figura 31 (A)unclassified
“…Já em HBSS sem adição de albumina sérica o tempo de conversão foi de 16,2 min, e com a adição de albumina sérica foi de 8,8 min. Esses resultados não somente confirmam a influência da albumina sérica no processo de isomerização (Zoerner et al, 2011;Garst et al, 2015;Kantae et al, 2017), mas também ressaltam a rapidez da conversão de 2-AG para 1-AG.…”
Section: De Acordo Com Publicações Utilizando Os Meios "Roswell Park unclassified
See 1 more Smart Citation